EFEKTIVITAS KOMUNIKASI DAN KOORDINASI SEKOLAH DALAM MENINGKATKAN PARTISIPASI ORANG TUA PADA IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 9 PEDUNGAN - Gede Agung, Anak Agung; Chindytia; Ni Komang Ayu Sari Pratiwi; Ni Kadek Nova Senja Pratiwi; Ni Kadek Eliana Vebianti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of school communication and coordination on parental participation in the implementation of School-Based Management (SBM) at SD Negeri 9 Pedungan, Denpasar. The research uses a descriptive quantitative approach with the support of qualitative data. The research instrument was in the form of a 5-point Likert scale questionnaire consisting of 30 statements and given to 15 teachers as respondents. Supporting data was obtained through semi-structured interviews with principals, curriculum representatives, and school committees. The results showed a communication index of 4.09, a coordination index of 3.95, and a parental participation index of 3.74 in the good category. The Pearson correlation test showed a strong positive association between parental communication and participation (r = 0.71; p < 0.01) and parental coordination and participation (r = 0.64; p < 0.05). The findings of the study confirm that open communication, consistency of tripartite meetings, and dialogical leadership are important factors in increasing parental involvement in the implementation of SBM in primary schools. Keywords: School Communication, Coordination, Parent Participation, School-Based Management, Elementary School.